Nuevo registro de Meoma ventricosa grandis GRAY,1851 (Echinodermata:Echinoidea,Bríssidae) - Buitrón Sanchez, Blanca Estela; Alonso Solis Martin, Fco.; Estela Buitrón Sanchez, Blanca Estela; Laguarda- Figueras, Alfredo (Coloquios de Paleontología, 1999)
A single spccimen of the species Meoma ventricosa grandis CRAY, 1851, frorn the lower Pliocene-Marcos Formation beds of Carmen Island in the Gulf of California was studied. It constitutes a new fossil record of the surispecies in the early Pliocene of Mexico, The speciíuen was found associated with calcareous algae, corals, bivalves (Pe<-ten ¿md Chione) and other echinoids. The paleontological setting for this fauna was that of a shallow and tropical sea.